Effectiveness of a nordic training protocol on muscle power in soccer players of club deportivo la equidad seguros (2016)
Introduction: Nordic training has been designed to optimize the sporting movement and prevent injuries in soccer players. However, there are no reports on studies that demonstrate its effectiveness on the explosive power of such sport. Objective: To determine the effectiveness of a Nordic training protocol on the explosive force of lower limbs in soccer players. Materials and methods: A randomized controlled study was performed, in which 26 male players were chosen to be part of an intervention group (n=12) and a control group (n=14). The intervention group was applied a Nordic training protocol, while the control group followed a conventional strengthening program. The explosive force of lower limbs was evaluated through the Bosco and Abalakov tests on a jumping platform, as well as the angle of greater biceps femoris muscle recruitment while performing the Nordic exercise through surface electromyography. Results: Both groups were homogeneous. An improvement was evident in the components of the explosive force (p less than 0.05) for takeoff speed, the motor recruiting and the peak registration of angle recruitment variables in the intervention group. Conclusion: The implementation of a training program in soccer players proved to be effective by positively influencing the variables involved in the explosive force. © 2016, Universidad Nacional de Colombia. All rights reserved.